Modeling Services Liberalization: The Case of Tanzania - Jensen, Jesper; Rutherford, Thomas F.; Tarr, David G. (2012)
Despite economic theory and empirical literature that have shown that wide availability of business services contributes significantly to productivity gains and growth, economic modelers have been slow to meaningfully incorporate services into their models. This paper employs a 52-sector, small, open-economy computable general equilibrium model of the Tanzanian economy to assess the impact of the liberalization of regulatory barriers against foreign and domestic business service providers in Tanzania. The model incorporates foreign direct investment in services, and productivity effects in both goods and services markets endogenously through a Dixit-Stiglitz framework. The paper summarizes and builds on the surveys and policy notes of the regulatory regimes in business services in Tanzania, and estimates the ad valorem equivalent of barriers to foreign direct investment. The paper estimates significant gains to Tanzania from services reforms, especially in banking, maritime and road transportation. Decomposition exercises reveal that the largest gains will derive from liberalization of non-discriminatory regulatory barriers.